Pengawasan Pertambangan Batubara Terhadap Kegiatan Reklamasi di Kota Samarinda - Andi Arief Rachman; Muhammad Jamal Amin; Mohammad Taufik (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
In coal mining, reclamation activities must be carried out by holders of mining business permits. In Samarinda City, there are 3 institutions that carry out reclamation oversight, namely the Ministry of Energy and Mineral Resources (Director General of Mineral and Coal), the Office of Energy and Mineral Resources of East Kalimantan Province and the Regional Reclamation and Post-mining Supervisory Commission. There are 3 main oversight mechanisms, namely, setting standards, observing facts in the field, comparing facts and formulating suggestions. Barriers encountered in supervising reclamation included limited human resources, funds, time, inactive status of mining companies, inactive supervisory bodies, changes in policies on minerals and coal. From the results of this study reclamation supervision is felt to be not optimal due to the lack of supervisors who are directly tasked with monitoring mining locations, difficult access and very long distances make monitoring difficult to carry out. The latest Law on Minerals and Coal has become one of the obstacles for local governments to carry out supervision, this is because the authority of local governments has been revoked. Minimal and sub-optimal supervision has resulted in damage to nature in Samarinda City, adverse impacts in the form of damage to the natural environment, damage to natural ecosystems, abandoned mine pits that have claimed as many as 39 people died in mining pits (voids).